2011
DOI: 10.1016/j.jad.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the lack of association between cognitive complaints and objective cognitive functioning in patients with bipolar disorder moderated by depressive symptoms?

Abstract: Cognitive complaints are not associated with objective cognitive functioning, irrespective of depressive symptoms. However, cognitive complaints are indicative for depressive symptoms. Clinicians should be to be alert to depressive symptoms rather than objective cognitive problems in patients expressing cognitive complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 33 publications
10
31
0
1
Order By: Relevance
“…In the sub-analysis in the present study, however, the CFQ showed no correlation with objective measures of cognitive dysfunction. This is consistent with two other studies (Burdick et al, 2005;van der Werf-Eldering et al, 2011) of which one study compared objective cognitive dysfunction with three self-rated cognitive inventories, including the CFQ, and none of the inventories showed an association with objective cognitive dysfunction (Burdick et al, 2005). The same study also found a strong correlation between the three self-reports suggesting a true absence of a correlation between subjective and objective cognitive dysfunction.…”
Section: Correlations Between Subjective and Objective Cognitive Funcsupporting
confidence: 88%
“…In the sub-analysis in the present study, however, the CFQ showed no correlation with objective measures of cognitive dysfunction. This is consistent with two other studies (Burdick et al, 2005;van der Werf-Eldering et al, 2011) of which one study compared objective cognitive dysfunction with three self-rated cognitive inventories, including the CFQ, and none of the inventories showed an association with objective cognitive dysfunction (Burdick et al, 2005). The same study also found a strong correlation between the three self-reports suggesting a true absence of a correlation between subjective and objective cognitive dysfunction.…”
Section: Correlations Between Subjective and Objective Cognitive Funcsupporting
confidence: 88%
“…The result was in accordance to that of the study of Burdick et al (2005). But other previous studies assessing the relationship between subjective and objective cognitive measures have shown controversial results (Burdick et al, 2001;Aydemir and Kaya, 2009;Arts et al, 2011;van der Werf-Eldering et al, 2011;Svendsen et al, 2012). Therefore, the findings suggest that most bipolar patients demonstrate objective signs of cognitive impairment, but they are unable to report them accurately.…”
Section: Discussionsupporting
confidence: 89%
“…Acute mania is reported to adversely affect impulse control (Ryan et al 2012 ) and executive function (Dixon et al 2004 ). Acute bipolar depression is associated with an attentional bias (Holmes et al 2008 ) with lowering of mental speed, impaired attention in general (van der Werf-Eldering et al 2010 ;Liu et al 2002 ) and verbal fl uency (Chaves et al 2011 ), verbal recall and fi ne motor skills impairment (Malhi et al 2007a ). In both acutely depressed and manic patients, impaired performance on theory of mind tests was found, even when memory was controlled for (Kerr et al 2003 ).…”
Section: The Effect Of Mood Symptomsmentioning
confidence: 99%
“…These include the possible adverse effect of brain white matter lesions that are sometimes found in remitted BD patients and in patients with schizophrenia but apparently do not underlie cognitive defi cits per se (Krabbendam et al 2000 ). Similarly, a lifetime comorbid alcohol use disorder, also does not seem to correlate with neurocognitive performance (van der Werf-Eldering et al 2010 ).…”
Section: The Role Of Other Clinical Factorsmentioning
confidence: 99%
See 1 more Smart Citation